2014
DOI: 10.1603/ec14142
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity and Transmission of <I>Xylella fastidiosa</I> by <I>Philaenus spumarius</I> (Hemiptera: Aphrophoridae) in Apulia, Italy

Abstract: Discovery of Xylella fastidiosa from olive trees with "Olive quick decline syndrome" in October 2013 on the west coast of the Salento Peninsula prompted an immediate search for insect vectors of the bacterium. The dominant xylem-fluid feeding hemipteran collected in olive orchards during a 3-mo survey was the meadow spittlebug, Philaenus spumarius (L.) (Hemiptera: Aphrophoridae). Adult P. spumarius, collected in November 2013 from ground vegetation in X. fastidiosa-infected olive orchards, were 67% (40 out of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
167
1
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(186 citation statements)
references
References 16 publications
1
167
1
17
Order By: Relevance
“…Purcell (1980) and Saponari et al (2014) also confirmed that P. spumarius was a vector of this bacterium to plants. In addition, Clastoptera achatina (Clastopteridae) and Lepyronia quadrangularis (Aphrophoridae) were shown to transmit X. fastidiosa to pecans (Sanderlin and Melanson 2010).…”
mentioning
confidence: 56%
“…Purcell (1980) and Saponari et al (2014) also confirmed that P. spumarius was a vector of this bacterium to plants. In addition, Clastoptera achatina (Clastopteridae) and Lepyronia quadrangularis (Aphrophoridae) were shown to transmit X. fastidiosa to pecans (Sanderlin and Melanson 2010).…”
mentioning
confidence: 56%
“…2a). In this model, the first two components give R 2 = 0.71 and Q 2 = 0.55, t [1] and t [2] accounting for 56 and 15% of the explained variance, respectively. The PCA model of Fig.…”
Section: Multivariate Statistical Analyses On Nmr Datamentioning
confidence: 99%
“…The PCA model of Fig. 2b is built with all the treated Ogliarola salentina and Cellina di Nardò samples, and the first two components give R 2 = 0.71 and Q 2 = 0.59, describing the samples distribution in the bidimensional space defined by t [1] and t [2] (in this case accounting for 53 and 18% of the explained variance, respectively). Analysis of the PCA (t[1]/t [2]) score plots showed that only in the case of samples treated with DENTAMET ® , a clear partition of data was observed with a good grouping according to the original cultivar (Ogliarola salentina and Cellina di Nardò).…”
Section: Multivariate Statistical Analyses On Nmr Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new paradigm of a non-persistent X. fastidiosa transmission mechanism was proposed, suggesting an egestion-salivation mechanism of pathogen inoculation [75]. In OQDS outbreaks, Philaenus spumarius (Hemiptera, Aphrophoridae) was rapidly identified as the most important vector for CoDiRO strain transmission [76,77]. The CoDiRO strain was also detected in other insects, such as Neophilaenus campestris (Aphrophoridae) and Euscelis lineolatus (Cicadellidae) [78,79], while sharpshooters may transmit subspp.…”
Section: Disease Monitoring and Widespread Distribution Of Pathogensmentioning
confidence: 99%